Sociology : a global perspective - Joan Ferrante (New Delhi Cengage Learning India Pvt. Ltd., 2015)
Sociological imagination; Sociological perspectives and methods of research; Culture; Socialization; Social structure and social interaction; Deviance, conformity, and social control; Social inequality; Race; Gender and sexualities; Economic and politics; Family; Education.
Keywords: Sociology